SENTRA WISATA KULINER KHAS KOTA PONTIANAK - Noviandi, Noviandi; Pebriano, Valentinus; Muazir, Syaiful (JMARS: Jurnal Mosaik Arsitektur, 2022)
Pontianak has numbers of culinary tourism potentials. The diversity factor and the significant development of culinary tourism have the potential to become the branding of Pontianak. Currently, the rise of fast food culinary and the absence of a representative culinary tourism container is a challenge for the development of culinary tourism in Pontianak. The design of Pontianak typical culinary tourism center can be the answer to these problems. The right location in the city's arterial road area and near settlements for easy access to the location and easy to identify. The choice of location is on Jalan Letkol Sugiono, South Pontianak District. The design starts from the analysis of commercial, recreational and educational functions. The design method consists of five stages, namely the idea stage, data collection, analysis, synthesis and design. The result of the design is a culinary tourism center with five floors. Space division based on space program and space hierarchy. The application of the neo vernacular theme is manifested in the composition, facade, and interior of the building.